Severe Left Ventricular Dysfunction in Falciparum Malaria: A Case Report and Review of Literature on Cardiac Involvement in Malaria - Chaudhary, N; Verma, N; Bhatia, BD; Gupta, BK; Kabiraj, N; Lodha, R (Journal of Universal College of Medical Sciences, 2013)
Malaria is an important cause of death in both children and adults, especially in tropical countries like India1. Nearly one third cases of malaria are reported from South Asia where majority (65%) of them are from India alone 1,2. If undiagnosed and untreated promptly, falciparum malaria can be an important cause for high case fatality rate. Cerebral malaria is one of the commonest causes of death in children1. Although involvement of myocardium and cardiac failure is rare, few cases have been reported in literature. We report a 10-year old male child diagnosed as falciparum malaria with severe left ventricular dysfunction. DOI: http://dx.doi.org/10.3126/jucms.v1i3.8766 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 53-55